Economic Evaluation of Expanding HPV Vaccination Programs for Boys: A Systematic Review - Ditya Tiwi Syafira; Dwi Endarti; Postma, Marteen J. (Journal of Health Economic and Policy Research (JHEPR), 2024)
Background: Human papillomavirus is responsible for almost all cases of cervical and non-cervical cancers. Various treatments have been carried out, but they have not been effective enough in reducing the burden. The U.S. Food and Drug Administration has approved three HPV vaccines for use. Since its recommendation in 2006, HPV infections have significantly decreased by 88% among teen girls and 81% among young adult women. Additionally, research has indicated that HPV vaccine is cost-effective in preventing both cervical and non-cervical cancers. The primary target group of HPV vaccination is girls aged 9-14, but some countries are starting to expand their programs according to the WHO recommendation for secondary targets: boys and adult women. This study gave updated information regarding the expansion of HPV vaccination programs for boys. Objective: To systematically review the health economic studies to evaluate the cost-effectiveness of expanding HPV vaccination program for including boys to prevent HPV-related cancer. Method: An electronic literature search was performed on two databases (Pubmed and ScienceDirect) to identify studies published from 2013 to 2023 in English and Indonesian. Three search strategies were used, including the terms «economic evaluation», «HPV», and «boys». The screening and selection of the literature was performed according to the PRISMA statement. Results: A total of 306 articles were identified. Only 26 of them were deemed relevant. This research compiled studies from countries with varying economic levels on the expansion of vaccination programs in boys to prevent or reduce cervical, anogenital, and HNC cancers. All the studies used a modeling approach to estimate the number of cases averted and the health care costs. Sixteen studies found that it was cost-effective to expand HPV vaccination programs to include boys. The ICER values were found to be sensitive to the vaccine price, duration of protection, and vaccination coverage. Conclusion: Expanding HPV vaccination to boys is considered a cost-effective solution for preventing HPV-related cancers, based on studies conducted in many countries. It is recommended to conduct an economic evaluation to estimate the cost-effectiveness of HPV vaccination as a prevention method for HPV-related cancers in low and middle-income countries like Indonesia. To begin the study, it is suggested to expand the HPV vaccination target to boys with a lower-priced vaccine and increased vaccination coverage.